Trigeminal Contributions to the Dorsal Cochlear Nucleus in Mouse - Balmer, Timothy S.; Trussell, Laurence O. (Frontiers in Neuroscience, 2021)
The dorsal cochlear nucleus (DCN) is the first site of multisensory integration in the auditory pathway of mammals. The DCN circuit integrates non-auditory information, such as head and ear position, with auditory signals, and this convergence may contribute to the ability to localize sound sources or to suppress perceptions of self-generated sounds. Several extrinsic sources of these non-auditory signals have been described in various species, and among these are first and second order trigeminal axonal projections. Trigeminal sensory signals from the face and ears could provide the non-auditory information that the DCN requires for its role in sound source localization and cancellation of self-generated sounds, for example, head and ear position or mouth movements that could predict the production of chewing or licking sounds. There is evidence for these axonal projections in guinea pigs and rats, although the size of the pathway is smaller than might be expected for a function essential for a prey animals’ survival. However, evidence for these projections in mice, an increasingly important species in auditory neuroscience, is lacking, raising questions about the universality of such proposed functions. We therefore investigated the presence of trigeminal projections to the DCN in mice, using viral and transgenic approaches. We found that the spinal trigeminal nucleus indeed projects to DCN, targeting granule cells and unipolar brush cells. However, direct axonal projections from the trigeminal ganglion itself were undetectable. Thus, secondary brainstem sources carry non-auditory signals to the DCN in mice that could provide a processed trigeminal signal to the DCN, but primary trigeminal afferents are not integrated directly by DCN.